Identification of the state-space dynamics of oil flames through computer vision and modal techniques. Issue 5 (1st April 2015) - Silva, R.P.; Fleury, A.T.; Martins, F.P.R.; Ponge-Ferreira, W.J.A.; Trigo, F.C.
Highlights This paper presents a new approach to estimate unstable flame dynamics. Computer vision processed images from CCD cameras provide a discriminant characteristic vector. A four-degree-of-freedom second order model is identified through Operational Modal Analysis. Unstable and stable flame models are cross-validated through spectral analysis. The method is capable of predicting flame extinction.